IgA pemphigus showing IgA antibodies to desmoglein 1 and 3 - Salama Hegazy (Mattioli1885, 2016)
Background: IgA pemphigus is a rare autoimmune vesiculo-pustular skin disease. Only approximately 70 cases have been reported to date. We report a case of IgA pemphigus with IgA antibodies to desmoglein 1 (Dsg1) and desmoglein 3 (Dsg3).